2020
DOI: 10.1177/1012690219897549
|View full text |Cite
|
Sign up to set email alerts
|

“If I’m sailing with a girl, I get identified as a ‘marshmallow’ ”: Gendered practices of school sport sailing in Western France and California

Abstract: Gendered divisions and representations can be especially problematic issues underpinning participation in water-based lifestyle and sporting activities. Sailing has particularly been found to be dominated by male participants who tend to dictate everyday codes of practice and symbolic representation. Female sailors are therefore regularly portrayed as inauthentic members of this activity and their participation also typically reflects much lower rates than males. In this paper, we develop these critical ideas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…To check the methodological quality of the studies, the analysis of the quality of the four qualitative articles evaluated in the research showed that two articles obtained a high score of 13 points or more out of a total of 21 items, with one article achieving the maximum score of 15 points [23], followed by Schmitt et al [42] with 13 points. Two qualitative articles, however, were below the threshold of 10 points, namely Machota-Blas [40] with five points, as well as Santos et al [41], so it could be understood that the quality of their papers is low.…”
Section: Analysis Of the Methodological Quality Of The Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…To check the methodological quality of the studies, the analysis of the quality of the four qualitative articles evaluated in the research showed that two articles obtained a high score of 13 points or more out of a total of 21 items, with one article achieving the maximum score of 15 points [23], followed by Schmitt et al [42] with 13 points. Two qualitative articles, however, were below the threshold of 10 points, namely Machota-Blas [40] with five points, as well as Santos et al [41], so it could be understood that the quality of their papers is low.…”
Section: Analysis Of the Methodological Quality Of The Studiesmentioning
confidence: 99%
“…Two qualitative articles, however, were below the threshold of 10 points, namely Machota-Blas [40] with five points, as well as Santos et al [41], so it could be understood that the quality of their papers is low. However, in a qualitative observation, and regardless of the scale used, the article by Machota-Blas [42] is a descriptive article of a teaching experience that is well presented and documented. In contrast, Santos et al's research [41] delineates collaborative efforts across multiple schools in Portugal aimed at crafting a curriculum centered on life skills via the medium of surfing.…”
Section: Analysis Of the Methodological Quality Of The Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ltd. ( 2012), sailing is predominantly a man's sport and it's required to be wealthy to deal with it. Because of the deep-rooted yet dehistoricized somatic codes, sailing has been assumed as a maledominated special interest (Schmitt et al 2020). To prove participation of the woman in yachting should be proved by performing a further study evaluating the owner-shipping, chartering, skippering, or just attending the cruises or sports activities.…”
Section: Figure 1 Frequencies For the Desired Yacht Typesmentioning
confidence: 99%